Developing A Learning Video for Introduction to Computer Components in Class VII Informatics Subjects Using Canva at SMPN 7 Bukittinggi - Yanti, Rahma; Chan, Fajri Rinaldi; Annas, Firdaus (BiCED Proceeding, 2023)
This research proposes the development of learning videos as an innovative and effective tool in supporting the introduction of computer components for class VII students at SMPN 7 Bukittinggi in the Informatics subject. Currently, in the world of education, especially amidst technological advances, it is important to utilize learning tools that are appropriate to the times. Using the Canva platform is a relevant choice in developing learning materials. The Canva platform is an intuitive and easy-to-use graphic design tool. In this context, Canva can be used to create interesting and interactive learning materials, such as images, diagrams and graphs, which will help students understand computer components better. Learning videos also allow students to learn independently, at their own pace. It is important to remember that an introduction to computer components is an important basis in Informatics lessons. Through learning videos, teachers can provide clear and visual explanations about these components, such as CPU, RAM, motherboard, and others. Students will be more engaged in learning and have references that can be accessed at any time. By combining learning video technology and creativity in using Canva, it is hoped that the results of this research will strengthen the quality of education at SMPN 7 Bukittinggi. This can also be an example of how technology can be used to support more effective and interesting learning in this digital era.